The Dynamics of Power Relations and Resistance Typology in Sorkin’s The Trial of the Chicago 7 - Farhan Iqbal Prasetyo (CV. Era Digital Nusantara, 2025)
The dynamic between governmental power and social movements is a recurring theme in historical cinema, exemplifying the persistent struggle against systemic authority. The Trial of the Chicago 7 vividly portrays this friction through the unequal relationship between the Nixon-era government and the Anti-Vietnam War Social Movement. Although power and resistance in cinematic narratives are frequently explored, limited research systematically integrates Michel Foucault’s concepts of power relations with Hollander and Einwohner’s multi-dimensional resistance typology to dissect the specific, underlying nature of these historical conflicts. Therefore, this study aims to examine the complex power dynamics and classify the resulting acts of resistance depicted within the film. Employing a qualitative descriptive method, the research analyzes the film's visual narrative and its script, evaluating the data through Foucault’s framework and Hollander and Einwohner’s three core resistance parameters: the actor's intent, the target's recognition, and the observer's recognition. The analysis identifies eight explicit instances of governmental power exertion (five by government officials and three by law enforcement) designed to suppress the movement's morale. In response, the study classifies 16 distinct acts of resistance based on the three parameters: nine instances of overt resistance, three of target-defined resistance, one of external-defined resistance, one of attempted resistance, and two instances of missed resistance. These results demonstrate that a repressive, Panopticon-like governmental power inevitably triggers complex, systemic forms of resistance from activists. At last, the study highlights that resistance is not monolithic. It is a multifaceted phenomenon shaped entirely by who intends it and who recognizes it within the social arena.